Manajemen Strategi Dalam Upaya Peningkatan Kinerja Guru Melalui Supervisi Akademik - Karoso, Subianto (Mahesa Research Center, 2024)
The existence of an educational institution lies in the quality of human resources created by the institution. This study focuses on the strategic management role of school principals to improve the quality of Human Resources (HR) management in an effort to improve teacher performance through academic supervision. This research uses the Systematic Literature Review (SLR) method where researchers review and identify journals in a structured and analyzable manner which is carried out in depth from scientific literature according to the research topic with the aim of increasing understanding regarding the research topic used. As for the literature used to strengthen the results of the analysis, researchers succeeded in identifying 30 articles or journals indexed by Sinta and several others found on Google Scholar related to strategic management in efforts to improve teacher performance through academic supervision carried out by school principals. Thus, from the 30 articles it could be filtered and 8 articles were found that were suitable, and the other 22 articles were excluded. Because this research focuses on strategic management in an effort to improve teacher performance through academic supervision. The results obtained are able to determine the role of the school principal in improving teacher performance through academic supervision.